Scalable Manufacturing of Large and Flexible Sheets of MXene/Graphene Heterostructures. Issue 5 (6th March 2019) - Zhao, Meng‐Qiang; Trainor, Nicholas; Ren, Chang E.; Torelli, Michelle; Anasori, Babak; Gogotsi, Yury
Abstract: Stacking different 2D materials is a promising strategy to fabricate heterostructures that combine the advantages and eliminate the associated shortcomings of individual building blocks. When used for energy storage, 2D heterostructures provide the opportunity to manufacture flexible and conductive paper electrodes, which require no binders, conductive additives, or current collectors. Here, 2D MXene/graphene heterostructured papers are manufactured by alternately stacking Ti3 C2 T x MXene and reduced graphene oxide (rGO) nanosheets using spray‐assisted layer‐by‐layer assembly. Up to letter paper–sized free‐standing films can be manufactured within half an hour of spraying. When used directly as anodes for Na‐ion storage, the MXene/rGO heterostructured films exhibit improved electrochemical performance compared to pure MXene and rGO films in terms of capacity, rate performance, and cycling stability. Capacities of ≈600 mAh g −1 are achieved by the Ti3 C2 T x MXene—20 wt% rGO heterostructured films at 0.25 C (≈220 mAh g −1 at 2.5 C) along with excellent cycling stability. This work demonstrates the advantages of 2D heterostructures and possibility of large‐scale manufacturing of MXene‐based materials for energy, separation, electromagnetic interference shielding, and biomedical applications. Abstract : 2D Ti3 C2 T x MXene/graphene heterostructured papers up to a letter size are manufactured using a spray‐assisted layer‐by‐layer assembly. These 2D heterostructured papers are free‐standing, flexible, and highly conductive. They can serve directly as electrodes for Na‐ion storage and exhibit high capacities along with good cycling stability and rate performance.